miR-124-3p Suppresses the Invasiveness and Metastasis of Hepatocarcinoma Cells via Targeting CRKL - Majid, Abbasi; Wang, Jinxia; Nawaz, Muhammad; Abdul, Sattar; Ayesha, Munawar; Guo, Chunmei; Liu, Qinglong; Liu, Shuqing; Sun, Ming-Zhong (Frontiers in Molecular Biosciences, 2020)
Abnormal expressions of microRNAs are involved in growth and progression of human cancers including hepatocellular carcinoma (HCC). An adaptor protein CRKL, plays pivotal role in HCC growth, whereas miR-124-3p downregulation is associated with clinical stage and the poor survival of patients. However, the relationship between miR-124-3p and CRKL and the molecular mechanisms through which they regulate HCC metastasis remains unclear. In the current work, we explored miR-124-3p and its correlation with CRKL protein expression in HCC patient tissues. We found that miR-124-3p deficiency is inversely co-related with CRKL overexpression in tumorous tissues of HCC patients, which was also consistent in HCCLM3 and Huh7 HCC cell lines. Target validation data shows that miR-124-3p directly targets CRKL. The overexpression of miR-124-3p reverses the CRKL expression both at mRNA and protein level and inhibits the cell development, migration, and invasion. Mechanistic investigations showed that CRKL downregulation suppresses the ERK pathway and EMT process, and concomitant decrease in invasion and metastasis of HCC cells. The expressions of key molecules in ERK pathway such as RAF, MEK, ERK1/2 and pERK1/2 and key promoters of EMT such as N-cadherin and vimentin, were downregulated. Whereas, the E-cadherin, a key suppression indicator of EMT was upregulated. MiR-124-3p-mediated CRKL suppression led to BAX/BCL-2 increase and C-JUN downregulation, which inhibited the cell proliferation and promoted the apoptosis in HCC cells. Collectively, our data illustrates that miR-124-3p acts as an important tumor-suppressive miRNA to suppress HCC carcinogenesis through targeting CRKL. The miR-124-3p-CRKL axial regulated pathway may offer valuable indications for cancer research, diagnosis and treatment.